IKRAR U DULUWO LIMO LO PAHALAA: BENTUK KESADARAN ETNIS GORONTALO ERA PRAKOLONIAL - Damis, Mahyudin (HOLISTIK, Journal Of Social and Culture, 2016)
This writing talk about the process of forming awareness ethnic Gorontalo the era of pre colonial. Start of collective awareness the community Lima Pahalaa be in the form of pledge or promise for living at peace between one of royal Gorontalo and Limboto a hostile for nearly two centuries. The purpose of this writing that, on one side the reader should understand that depart from a start of collective awareness, of ethnic groups Gorontalo by ingenious take advantage of momentum which â€œavailable â€œ in order to break away from the conditionÂ  â€œdependence â€œ the military of another ethnic group, and they shall also out of â€œpolitical dominanceâ€ outside on the other hand. Start of collective awareness ethnic Gorontalo articulated in the form of â€œFellowship U Duluwo Lo Limo Lo Pahalaaâ€ brokered by figures khatibi daâ€™a Eyato of Gorontalo and Popa of Limboto. Keywords: awareness, ethnic, colonial